Analisis Komparasi Potensi Kebangkrutan Dengan Metode Altman Z-Score, Springate, Dan Zmijewski (Studi Pada Perusahaan Manufaktur Sub Sektor Tekstil Dan Garment Yang Terdaftar Di Bursa Efek Indonesia Periode 2017-2019) - Norliyana Norliyana; Budi Wahono; Achmad Agus Priyono (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
Abstract The purpose of this research is to determine the comparability in predicting potential bankruptcy using the Altman Z-Score, Springate, and Zmijewski methods and the accuracy of the three methods.The method in this research is purposive sampling with criteria needed by researchers to be able to obtain sample. Samples obtained from the BEI for the period 2017 to 2019 were 17 companies. The data used are secondary data.The results of data analysis showed that there were differences in the results of bankruptcy predictions between the Altman Z-Score, Springate, and Zmijewski methods. From the results that the Zmijewski method is the method that has highest accuray rate 64,71%Keywords: Bankruptcy, Altman Z-Score method, Springate method,and Zmijewski method